ELEMENTS IN MOVIE TRAILERS THAT MOTIVATES AUDIENCE TO WATCH MOVIES IN MALAYSIA - Abu Bakar, Mohd Syuhaidi; Bolong, Jusang; Bidin, Rosmiza; Ayub, Nur Syuhaidah; Shuki, Mohamad Syafiq Bin Mat; Jono, Siti Nor Fazira (International Journal of Psychosocial Rehabilitation, 2020)
Marketing is one of the main drivers of the performance of a movie and positively influences box-office success even if the product is poor. Thus, filmmakers increasingly depend on movie trailers as an advertising platform. But what is the essential element that makes a good movie trailer? This paper has analysed the elements embedded in a movie trailer that has motivated Malaysian audiences to watch a movie. Qualitative research methods were used and 15 informants from different backgrounds were interviewed in a face to face session. The data were then transcribed and the result was transformed into a conceptual framework. Eight elements (Cinematography, Audio, Colour, Storylines, Genre, Picture, Director, and Actor) were mentioned by the informants. These findings will be able to assist filmmakers and film distributors in Malaysia to emphasize on specific movie trailer elements before planning the promotional campaigns of their movie.